Spin-polarized self-trapped excitons in low-dimensional cesium copper halide - Ruiqin Huang; Longbo Yang; Feng Yang; Yuttapoom Puttisong; Qingsong Hu; Guixian Li; Jingnan Hu; Zhaobo Hu; Liang Li; Jiang Tang; Weimin Chen; Yibo Han; et al. (Nature Communications)
Abstract Spin polarized excitons induced by spin injection from magnetic ion to a single quantum dot, has been considered as a basic unit of quantum information transfer between spin and photon for spin-photonic applications. However, this state-of-the-art technology has only been found with limited coupling strength and weak excitonic emission. Here, we demonstrate a spin-polarized self-trapped exciton naturally formed in the zero-dimensional lattice of cesium copper iodide. Upon excitation, the conversion from Cu+ ion to spin-1/2 Cu2+ ion results in an in-situ self-trapped exciton, which facilitates a local Jahn-Teller distortion and guarantees the strong spin-exciton coupling and near-unity excitonic emission efficiency. Consequently, a giant Zeeman splitting of −53 meV and an effective excitonic g-factor of −93.5 are observed from magneto-photoluminescence. More importantly, this nano-scale coupling can also be driven by an external electric field, which generates electroluminescence with a circular polarization of 44.5% at 4.2 K and 8% at 300 K. The spin-optic properties of this copper compound will stimulate the fabrication of next-generation spin-photonic devices based on self-trapped excitons.